2020
DOI: 10.5771/0949-6181-2020-3-418
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of Conflict Management Styles in Multinational Organisations: Empirical Evidence from Serbia

Abstract: This study explores the conflict management styles of German and Serbian managers in multinational organisations in Serbia. Contrary to most previous cross-cultural studies on conflict management styles, we have analysed not only the impact of the dimensions of individualism vs. collectivism on conflict management styles, but the effect of power distance dimension also. Moreover, none of the previous studies have analysed the conflict of management styles of managers in Southeast Europe, let alone the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Further to this, SMEs need support to develop and deploy innovative and imaginative solutions that can lead to full implementation of 5I model proposed in this article. Successful effort of Gulf Co-operation Council countries to build appropriate regulatory framework and support system might be a good example for the post-conflict countries integrated in similar forms of regional cooperations, such as Open Balkans countries: Republic of Serbia, Albania, and North Macedonia [40]. Such countries can increase their competitiveness and keep pace with the technological trends and developments [41], [16].…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, SMEs need support to develop and deploy innovative and imaginative solutions that can lead to full implementation of 5I model proposed in this article. Successful effort of Gulf Co-operation Council countries to build appropriate regulatory framework and support system might be a good example for the post-conflict countries integrated in similar forms of regional cooperations, such as Open Balkans countries: Republic of Serbia, Albania, and North Macedonia [40]. Such countries can increase their competitiveness and keep pace with the technological trends and developments [41], [16].…”
Section: Discussionmentioning
confidence: 99%
“…Research on conflict negotiations across power inequalities examines the impact of high and low relative power on processes, outcomes and behaviors (Tinsley, 2001;Coleman et al, 2010;Ristic et al, 2020). As power increases, one party becomes less dependent on its counterpart, enabling domineering behavior to achieve objectives (Lam and Chin, 2004;Nazir Butt and Nam Choi, 2010;Lu et al, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Thus, organizations headquartered in the USA may tend to define success (Katz et al , 1999) in different and predictable ways from those in more collectivist countries (Pagell et al , 2005). It has been suggested that factors defining national culture will result in systematic differences in creativity, innovation and social acceptance (Florida, 2005; Kim et al , 2004; Morris et al , 1998; Ristic et al , 2020). We believe examining the use of CMS cross-nationally within a single generation of workers will make a value-added contribution to the literature on conflict management.…”
Section: Conflict-management Strategies In a Global Settingmentioning
confidence: 99%